Indonesia's new president : coming crunch-test for Joko Widodo - Yang Razali Kassim (2014)
Joko Widodo has emerged from relative obscurity to be Indonesia's president-elect. Before taking power in October he must form a conpetent cabinet and strengthen his coalition to avoid leading a minority government. Will he succeed?